Pelatihan Kecakapan Kolaborasi Digital bagi Guru-Guru IPA Sekolah Menengah di Jawa Tengah - Muhammad Luthfi Hidayat; Dwi Setyo Astuti; Hariyatmi Hariyatmi; Harun Joko Prayitno; Sofyan Anif (Warta LPM, 2022)
Collaboration is one of the 21st-century skills that are important to be mastered by teachers or students in the school environment, especially in the scope of science learning (IPA). Science learning requires group and collaborative activities such as practicum in the laboratory for example. However, an outbreak of the Covid-19 pandemic has affected nearly 363.1 million children and adolescents worldwide due to school closures that make group activities and collaboration challenging to do. The outbreak of the Covid-19 pandemic has affected nearly 363.1 million children and adolescents worldwide due to school closures. Many teachers are turning to online classes and transforming their learning into a digital environment. The ability of every science teacher in conducting digital-based learning in terms of collaboration is are not the same, because not all have been prepared for this before. In Indonesia, there are no minimum competency standards that must be mastered by teachers to conduct online learning, including the competence to collaborate digitally. Especially for science teachers, practicum and collaboration in the laboratory cannot be carried out. In fact, laboratory practicum plays a role in increasing scientific competence apart from the transfer of knowledge. Based on these problems, the GutasiPetal (Digital-Competence Literacy for Teacher) team held online training on Digital CompetenceCompetency, particularly in digital collaboration, to strengthen and map the digital collaboration digital competencies of science teachers in Central Java. , as well as improve skills to collaborate online for science learning in a digital environment. The method for the training through Zoom Conference, synchronous simulation, and asynchronous group assignment. Therefore, for evaluating the collaboration skill of the teachers, we assessed the assignment work and analyzed questionnaire results using RASCH Analysis.